Determinan Permintaan Motor Kredit Pada PT. Federal International Finance (FIF) di Kabupaten Manokwari - Yuyun P. Rahayu; Elina R. Situmorang; Yospin Pasiamping (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
Purpose of this study is to analyze determinant factors influencing the demand for Honda motorcycle credit at PT. Federal International Finance (FIF) Manokwari Regency. Descriptive statistics analysis method is used. Data was collected by interviews and questionnaires. Data analysis was performed using multiple linear regression analysis tools. The results show that the growth of credit demand in Manokwari Regency from 2011 to 2014 showed an increase. This because the use of motorbikes are efficient and economical as transportation. Thus, people prefer to use it rather than other transportation, such as cars. Furthermore, result of this study is that of the four variables used (income, credit payment period, the price of substituted products and goods) simultaneously have a positive and significant effect on the demand for Honda motorcycle credit in Manokwari Regency. While partially, only the credit payment period does not affect the demand for Honda motorcyclecredit.